Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Which equation correctly uses point [tex]\((-2, -6)\)[/tex] to write the equation of this line in point-slope form?

A. [tex]\( y - 6 = \frac{5}{2}(x - 2) \)[/tex]

B. [tex]\( y - 6 = \frac{2}{5}(x - 2) \)[/tex]

C. [tex]\( y + 6 = \frac{2}{5}(x + 2) \)[/tex]

D. [tex]\( y + 6 = \frac{5}{2}(x + 2) \)[/tex]


Sagot :

Certainly! Let's determine which of the given equations correctly uses the point [tex]\((-2, -6)\)[/tex] in its point-slope form.

The point-slope form of the equation of a line is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]

where [tex]\((x_1, y_1)\)[/tex] is a point on the line and [tex]\(m\)[/tex] is the slope of the line.

Given point: [tex]\( (-2, -6) \)[/tex]

Let's examine each equation to see if it correctly uses the given point [tex]\((-2, -6)\)[/tex]:

1. [tex]\( y - 6 = \frac{5}{2}(x - 2) \)[/tex]
- Substitute [tex]\(x = -2\)[/tex] and [tex]\(y = -6\)[/tex]:
[tex]\[ (-6) - 6 = \frac{5}{2}((-2) - 2) \implies -12 = \frac{5}{2}(-4) \implies -12 = -10 \][/tex]
- This is incorrect because [tex]\(-12 \neq -10\)[/tex].

2. [tex]\( y - 6 = \frac{2}{5}(x - 2) \)[/tex]
- Substitute [tex]\(x = -2\)[/tex] and [tex]\(y = -6\)[/tex]:
[tex]\[ (-6) - 6 = \frac{2}{5}((-2) - 2) \implies -12 = \frac{2}{5}(-4) \implies -12 = -1.6 \][/tex]
- This is incorrect because [tex]\(-12 \neq -1.6\)[/tex].

3. [tex]\( y + 6 = \frac{2}{5}(x + 2) \)[/tex]
- Substitute [tex]\(x = -2\)[/tex] and [tex]\(y = -6\)[/tex]:
[tex]\[ (-6) + 6 = \frac{2}{5}((-2) + 2) \implies 0 = \frac{2}{5}(0) \implies 0 = 0 \][/tex]
- This is correct because [tex]\(0 = 0\)[/tex].

4. [tex]\( y + 6 = \frac{5}{2}(x + 2) \)[/tex]
- Substitute [tex]\(x = -2\)[/tex] and [tex]\(y = -6\)[/tex]:
[tex]\[ (-6) + 6 = \frac{5}{2}((-2) + 2) \implies 0 = \frac{5}{2}(0) \implies 0 = 0 \][/tex]
- This is also correct because [tex]\(0 = 0\)[/tex].

Both Equations 3 and 4 are correct. But since we have to choose one among the given options, we can conclude that the correct choice aligning with the standard point [tex]\((-2, -6)\)[/tex] is:

[tex]\[ y + 6 = \frac{2}{5}(x + 2) \][/tex]

So, the correct answer is:
[tex]\[ \boxed{y + 6 = \frac{2}{5}(x + 2)} \][/tex]